The Impact of Leadership Styles of School Principals on Teacher Performance - Kumari, H. M. Lalitha (Researchparks Publishing, 2023)
The purpose of this study was to investigate the impact of principals’ leadership styles on teacher performance in secondary schools in Colombo District Sri Lanka. The objectives of this study were to identify the leadership styles used by secondary school principals, find out level of teachers’ performance and explore the impact of principals leadership styles on teacher performance. The study was carried out in association with two hundred and fifty (250) sample units of secondary level teachers. Simple random sampling was used to select the sample. This research was quantitative in nature and the descriptive survey design was employed. A questionnaire was used as data collection instruments. The data analysis was done using Statistical Package for Social Sciences (SPSS) and presented using frequency, percentage, mean value, standard deviation, tables and graphs. Results revealed that there are two types of leadership styles of school principals, namely democratic and transformational leadership styles which have significant impact on teacher performance. Further, it was revealed from this study that more than 80% of secondary level principals use democratic and transformational leadership styles in their schools. In addition, 95% of teachers had positive perception on principals’’ leadership styles. Further it was found that there is a positive relationship between principals’ leadership styles and teacher performance. The study concluded that a significant number of secondary level teachers in Colombo District have positive perception about principals leadership styles. It is, therefore, recommended that, the school principals should use democratic and transformational leadership styles in order to increase work performance of teachers.